Evaluation of Glucosamine Effect Against Heart and Brain Damage Induced by Y-radiation or Aluminium Chloride in Female Rats - Hawas,Asrar Mohamed Mourad (2020)
Abstract Glucosamine is known as anti-inflammatory, antioxidant and as neuroprotective as well as using to treat many of diseases. This work aimed to investigate the remedial effect of glucosamine (20mg/kg b.wt) against the damage induced by a single dose of γ-radiation (8Gy) or aluminium chloride (AlCl3) (100mg/kg b.wt) in the heart and brain tissues of female rats. Serum aspartate aminotransferase (AST), cholesterol, triglycerides (TGs), LDH and creatine kinase (CPK) were measured. Moreover, gene expression of amyloid protein precursor (APP) and seladin-1 were estimated in the brain tissue. Also, acetylcholinesterase activity (AChE) and p-tau protein expression were estimated in brain homogenate. Metallothioneine (MT) was estimated in the heart and brain tissues. Heart and brain histopathological examination was performed. Irradiation significantly decreased serum AST, CPK and LDH, as well as MT levels in heart and brain tissues. Also, gene expression of seladin-1 decreased. On the other hand, irradiation significantly increased serum TGs level and brain AchE activity, tau protein, and β-amyloid percursor (APP). AlCl3 administration (21 days) induced disturbance in most of the estimated parameters, especially AST, TGs, and MT. Glucosamine treatment with irradiation or AlCl3 improved most of the measured parameters. In addition, histopathological examination confirmed the biochemical results. In conclusion: Glucosamine could be used to improve the heart and brain damages induced by γ-radiation exposure or AlCl3.